Arabic For Specific Purpose And Systematic Literature Review On The Design Of Islamic Tourism Mobile Application - Mohammad Najib Jaffar; Azman Ab Rahman; Mohd Nizwan Musling; Nurkhamimi Zainuddin; Siti Rosilawati Ramlan; Mohammad Imran Ahmad; Ghazali Zainuddin; Muhammad Sabri Sahrir (Universitas Islam Negeri Maulana Malik Ibrahim Mal, 2024)
Indexed by WOS